Prognostic significance of residual lymphovascular invasion after resection of locally advanced and borderline resectable pancreatic adenocarcinomas treated by neoadjuvant chemotherapy. Issue 8 (August 2021) - Addeo, Pietro; Fattori, Antonin; Grunder, Caroline; Dufour, Patrick; Averous, Gerlinde; Bachellier, Philippe
Abstract: Background: The current study aimed to identify histological prognostic factors after resection of locally advanced (LA) and borderline (BL) pancreatic adenocarcinomas treated by neoadjuvant chemotherapy (NC). Methods: A retrospective review was performed of patients with LA and BL adenocarcinomas operated after NC between January 2010 and April 2018. Prognostic factors for survival were assessed by multivariate Cox analysis. Results: Of the 84 patients, 29 had BL and 55 had LA pancreatic adenocarcinomas. Seventy-five patients underwent synchronous venous resection and 57 underwent arterial resection. The median overall survival from surgery was 21.10 months (BL 23-LA 21) (95% CI: 14.8–30.3) with 1-, 3-, and 5-year overall survival rates of 73%, 32%, and 20%, respectively. Multivariate analysis identified lymphovascular invasion (LVI) as an independent prognostic factor for overall survival (HR: 2.32, 95% CI: 1.28–4.22; p = 0.004). Patients without LVI (n = 37) had superior median overall and 5-year survival rates (31.0 months [40 from diagnosis]; 39%) compared to patients with LVI (n = 47; 14.4 months [22 from diagnosis]; 7%). The absence of residual LVI was associated with major pathologic response rates (p < 0.05). Conclusion: The persistence of LVI at pathology after resection of LA and BL treated by neoadjuvant chemotherapy predicts poor response and limited long-term survival.